2014
DOI: 10.5455/jeim.050913.or.089
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the polyphenol composition and antioxidant capacity of propolis and Echinacea purpurea

Abstract: This study was undertaken to evaluate and compare total phenolics and total flavonoides, and antioxidant capacity of propolis and Echinacea purpurea ethanol extracts. Methods: Propolis and dried Echinacea purpurea extracts were obtained by extraction methods. The extracts were tested for total phenol and total flavonoid contents and antioxidant capacity was determined by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. Results: The content of total phenolics and total flavonoids of propolis were found to be hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…400 mg chlorogenic acid equivalents/g extract [ 37 ] and approx. 350 mg GAE/100 g extract for the ethanolic extract [ 38 ], as presented by other authors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…400 mg chlorogenic acid equivalents/g extract [ 37 ] and approx. 350 mg GAE/100 g extract for the ethanolic extract [ 38 ], as presented by other authors.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of total flavonoids, other studies identified the presence of approx. 11 mg catechin equivalents/100 g ethanolic extracts [ 38 ] and between 10 and 33 quercitin equivalents/g dry weight for different parts of E. purpurea extracts grown in supplemented soil [ 40 ]. The total flavonoid content observed in this study was higher than the flavonoid contents reported by other authors [ 39 ], leading to the conclusion that the selected methods positively influenced the total flavonoid content.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a positive correlation between activity and the total phenol content was established. These phenolics exhibit their activity by different mechanisms such as reducing agents, hydrogen donors, singlet oxygen quenchers, and metal chelating agents (Georgieva, ChristovaBagdassarian, & Atanassova, 2014). Previous reports have indicated that methanolic and aqueous extracts impeded autoxidation of linoleic acid and the activity was attributed to the phenolic compounds present in B. oleracea aqueous extracts (Tanongkankit, Chiewchan, & Devahastin, 2010).…”
Section: Bioactivities Of the Brassica Plant Extractsmentioning
confidence: 99%
“…The antioxidant activity of E. purpurea extracts has been already reported in several studies. In this way, Georgieva, Christova‐Bagdassarian, and Atanassova () evaluated the antiradical capacity of an E. purpurea ethanol extract using the 2,2‐diphenyl‐1‐picrylhydrazyl (DPPH) assay. The antioxidant power was higher than that showed by ascorbic acid (vitamin C), and it was related to the total phenol content (353.6 mg gallic acid equivalents/100 ml).…”
Section: The Genus Echinacea Plants As Antioxidants and Food Preservamentioning
confidence: 99%
“…The antioxidant power was higher than that showed by ascorbic acid (vitamin C), and it was related to the total phenol content (353.6 mg gallic acid equivalents/100 ml). These components can act in several ways: as reducing agents, hydrogen donors, singlet oxygen quenchers, and metal chelating agents (Georgieva et al, ). Pellati, Benvenuti, Magro, Melegari, and Soragni () reported that methanol extracts of E. angustifolia , E. pallida , and E. purpurea roots as well as Echinacea herbal medicines scavenged the synthetic free radical DPPH (EC 50 from 104 to 2,165 μg/ml).…”
Section: The Genus Echinacea Plants As Antioxidants and Food Preservamentioning
confidence: 99%